A model system for sensitive detection of viable e. Coli bacteria combining direct viability pcr and a novel microarray-based detection approach - Lehniger, Lydia; Rudloff, Anne; Pollok, Sibyll; Grosse, Norman; Wessel, Kristin; Brendel, Monique; Popp, Juergen; Weber, Karina (Chemosensors, 2021)
We established an innovative approach that included direct, viability, and nested PCR for rapid and reliable identification of the fecal indicator organism Escherichia coli (E. coli). Direct PCR enabled successful amplification of the target uidA gene, omitting a prior DNA isolation or purification step. Furthermore, we applied viability PCR (v-PCR) to ensure the detection of only relevant viable bacterial cells. The principle involves the binding of propidium monoazide (PMA), a selective nucleic acid intercalating dye, to accessible DNA of heat killed bacteria cells and, consequently, allows viable and heat killed E. coli cells to be discriminated. To ensure high sensitivity, direct v-PCR was followed by a nested PCR step. The resulting amplicons were analyzed by a rapid 30 min microarray-based DNA hybridization assay for species-specific DNA detection of E. coli. A positive signal was indicated by enzymatically generated silver nanoparticle deposits, which served as robust endpoint signals allowing an immediate visual readout. The presented novel protocol allows the detection of 1 × 101 viable E. coli cells per PCR run.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Direct viability nested PCR; E. coli; Microarray-based DNA hybridization; Water monitoring